Propagation characteristics of the vortex beam array through anisotropic non-Kolmogorov maritime atmospheric turbulence - Yu, Hong; Yang, Bowen; Hu, Hanyin; Zhong, Zheqiang; Zhang, Bin (Frontiers in Physics, 2023)
By employing the power spectrum inversion method to generate phase screens of atmospheric turbulence over the sea, the theoretical model of the vortex beam array emitted by a focusing system through anisotropic non-Kolmogorov maritime atmospheric turbulence was built up. The propagation characteristics of the vortex beam array were investigated theoretically, and compared to those of the Gaussian beam array. On the basis, using the evaluation parameters including the relative beam width and the beam wander, the influences of various parameters of the vortex beam array and the atmospheric turbulence, such as the topological charge, beamlet width, number of beamlets, anisotropy factor, and power law, on its propagation characteristics through anisotropic non-Kolmogorov maritime atmospheric turbulence were studied extensively and compared to those of the Gaussian beam array. The results can provide useful reference for the applications of the vortex beam array in optical communication through maritime atmosphere.